PECULIARITIES OF GRAMMAR STUDY OF MOUNTAIN FIRST-FORM PUPILS - Marija Kiryk (Vasyl Stefanyk Precarpathian National University, 2015)
The articles describes the role of analiztor system (auditory, visual, kinesthetic) at the initial stage of learning literacy and language development six years old. They from specific integration system, that provides more efficient perception, memorization and reproduction of educational material. The article deals with attempt to ascertain linguadidactic interconnections and interdependence between grammar education (reading, writing) and speech of six-year pupils. Summing up it should be mentioned to organize 6-year pupils studing in the country mountain school becides pedagogical, economical, geographic and social problems psychologic linguadidactic are added. Preferences of mountain country children: -                    Formation from childhood ability to live in harmony with nature; -                    Sensitive  perception of alive and inanimate surrounding nature; -                    Life-style form children's responsibility for entrusted things, labour habits, training by hard nature conditions. They should be solved in complex providing achievents of psychology, pedagogics, linguists and up-to-date technology. The aim of the article  - to reveal individual peculiarities of country mountain child who needs special method of approach to grammar studing as well as to help country teacher who strongly feels lack for efficient method help. All these affect on prepearing level, children's outlook, general development. Scientific and methodogical institutions have not easy task-system training and skill raising of primary school teachers to realize State standart of primary general education. Acquaintance of country teacher with up-to-date achievements in psychologic, pedagogic and linguistic education will help him to organize his work in the country school on rather higher level as well as let him give more qualitative education services and save country school as the main country existent validity